Urban recreational fisheries: Implications for public health in metro-Phoenix. (June 2019) - Lucas, Daniel; Polidoro, Beth
Abstract: Lakes and ponds across metro-Phoenix primarily provide recreational opportunities for fishing, as swimming and other uses are generally not permitted. Given these designated uses, many of the lakes and ponds are monitored for nutrients and signs of eutrophication, but not necessarily for heavy metals or organic pollutants that can be transferred over time to recreationally-caught fish. This may be a concern considering the practice of many Phoenix residents who catch and consume fish from urban waterways. In this pilot study, samples of commonly stocked fish species (e.g. trout, bluegill, bass and catfish) and resident fish (sunfish) were collected through standard recreational fishing practices and analyzed for both metal and organic contaminants. Results showed varying concentrations of pesticides, polycyclic aromatic hydrocarbons (PAHs), and phthalates, as well as several potentially toxic metals. These findings may have long-term public health consequences, as approximately 60% of urban anglers have reported eating the fish they catch. Results from this study highlight the need for regular urban water and stocked fish monitoring, improved regulations to protect urban surface water quality, and creation of a comprehensive and standardized protocol for urban fish consumption advisories. Highlights: Recreationally-caught fishes in metro-Phoenix contain a wide range of pesticides, PAHs, phthalates and metals. Concentrations of mercury and aluminum in fishes in metro-Phoenix may pose a risk to human health. Oral reference doses for many organic contaminants may not be available. Fish consumption advisory programs vary widely by state, especially in urban areas.